Pengaruh Pelatihan Jump Rope dan Koinasi Jump Rope-Butt Kick Terhadap Daya Ledak Otot Tungkai Perenang Usia Dini pada Peserta Ekstrakurikuler Renang SDK Marsudirini - Gusti Agung Ayu Komang Ari Natasya Sastra Negara; Komang Ayu Krisna Dewi; Ni Gusti Ayulia Rusmayani (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of financial distress and auditor reputation on going-concern audit opinions in energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with secondary data obtained through documentation techniques on the company's annual financial statements and independent auditor reports. The research sample was determined using a purposive sampling technique based on certain criteria in accordance with the research objectives. Data were analyzed using logistic regression with the help of EViews 13 software. The results show that financial distress negatively affects going-concern audit opinions, while auditor reputation does not affect going-concern audit opinions. Simultaneously, financial distress and auditor reputation influence going-concern audit opinions. These findings indicate that a company's financial condition is a more dominant factor considered by auditors in issuing going-concern audit opinions than auditor reputation. This study provides implications for company management to maintain healthy financial conditions to reduce the risk of receiving going-concern audit opinions, and can be a consideration for investors in assessing the business continuity of energy sector companies.